Bel-Air Bambi and the Mall Rats - Peck, Richard (Bantam Doubleday Dell Books for Young Readers, 1995)
Bambi, Buffie, and Brick, three totally cool siblings from Los Angeles, move with their parents to Hickory Fork, a small town terrorized by a high school gang
Keywords: Moving, Household / Juvenile fiction; Gangs / Juvenile fiction; Schools / Juvenile fiction; Moving, Household / Fiction; Gangs / Fiction; Schools / Fiction; Humorous stories; Kleinstadt; Produktion; Fernsehfilm; Gewalttätigkeit; Schule; Alltag; Familie; Wohnungswechsel; Kooperation; Jugendbande; USA; Jugendbuch